EFFECT OF THE SHAPED MARKET ON THE ROAD SHOULDER ON THE PERFORMANCE OF ROAD SEGMENTS SUNGGUMINASA - BONTONOMPO - Harun, A Muh Yusuf; Agustang, Andi; Pertiwi, Nurlita (ASTONJADRO, 2022)
With the increasing demand for the fulfillment of the necessities of life, the shock market, which is located on the Sungguminasa - Bontonompo road section, is also developing slowly. The number of traders and buyers is increasing, the place to trade is wider and the transaction time is getting longer. Pasar Shock on the Sungguminasa - Bontonompo axis road is the only traditional market nearby and offers a relatively complete range of trading commodities within a 1 km radius of the settlement. With a relatively short distance and the attractiveness that the market is able to provide on the Sungguminasa - Bontonompo axis road. Apart from its very strategic location and high level of demand, the shock market on the Sungguminasa - Bontonompo axis road is also relatively easy to reach. This study aims to analyze the performance of the road on the capacity of traffic volume and the degree of saturation caused. The method used in this study is the Observation Method with data collection through direct observation in the field of the research object including data on the number of vehicles passing and one observation point is taken with different traffic flow directions. The results showed that the Sungguminasa-Bontonompo road network was still able to serve traffic transportation, the road capacity was = 2449 pcu/hour; volume of vehicle traffic = 3994 pcu/hour. The value of the degree of saturation DS = 1.63 so that it can be defined that the service level of the Sungguminasa-Bontonompo axis road belongs to category F or traffic jams, the speed is very low.